2022
DOI: 10.1002/eat.23706
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐studies systematic review of the experiences of body image, disordered eating, and eating disorders during the COVID‐19 pandemic

Abstract: Objectives This systematic review assessed the influence of the COVID‐19 pandemic and associated restrictions on body image, disordered eating (DE), and eating disorder outcomes. Methods After registration on PROSPERO, a search was conducted for papers published between December 1, 2019 and August 1, 2021, using the databases PsycINFO, PsycARTICLES, CINAHL Plus, AMED, MEDLINE, ERIC, EMBASE, Wiley, and ProQuest (dissertations and theses). Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
65
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 133 publications
(322 reference statements)
9
65
0
1
Order By: Relevance
“…Moreover, we found a slight decrease in the weighted pooled prevalence of screen-based disordered eating from the pre-COVID period of 2015–2019 (23.8%) to the post-COVID period (2020 onwards; 20.8%). Our data are consistent with several other recent reviews [ 167 , 168 ] in suggesting that a COVID-19 effect is accurate in some places and for some vulnerable people—and, in particular, people who already have an eating disorder—but not in general. Future research and meta-analytic reviews are needed to clarify the moderating and mediating variables at work here.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found a slight decrease in the weighted pooled prevalence of screen-based disordered eating from the pre-COVID period of 2015–2019 (23.8%) to the post-COVID period (2020 onwards; 20.8%). Our data are consistent with several other recent reviews [ 167 , 168 ] in suggesting that a COVID-19 effect is accurate in some places and for some vulnerable people—and, in particular, people who already have an eating disorder—but not in general. Future research and meta-analytic reviews are needed to clarify the moderating and mediating variables at work here.…”
Section: Discussionsupporting
confidence: 93%
“…People facing financial stressors may have also experienced fewer reported benefits of the pandemic, such as increased time for self‐care. Similarly, Schneider et al ( 2022 ) reported that people of Asian heritage with EDs reported higher psychological distress during COVID‐19, which could in part reflect increased discrimination and hate crimes against this group (see Supplemental Material for additional resources addressing this issue). These are important findings that can help guide screening and treatment to ensure we are reaching all individuals in need of care, many of whom do not fit the historical white, wealthy, cisgender/heterosexual stereotype of those affected by EDs/DE.…”
mentioning
confidence: 96%
“…The three reviews in this special issue (Devoe et al, 2022 ; Linardon et al, 2022 ; Schneider et al, 2022 ) illuminate the profound impact the COVID‐19 pandemic has had on people with eating disorders (EDs) or disordered eating (DE; i.e., distressing symptoms such as binge eating or body dissatisfaction) in Western countries (unfortunately, research in non‐Western contexts remains limited). The storm of the pandemic has brought with it increased stress, isolation, anxiety, body image concerns, and both DE and EDs that have led to a dramatic increase in hospitalizations for adults and youth (Devoe et al, 2022 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations